If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1y = 12 Solving X + -1y = 12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'y' to each side of the equation. X + -1y + y = 12 + y Combine like terms: -1y + y = 0 X + 0 = 12 + y X = 12 + y Simplifying X = 12 + y
| w^2+3w-54=0 | | 2(3-6)-3(5-x)=9 | | y=-x^2+4x-1 | | 135+3v(25+5)=v | | 10+n=16-2 | | (x-1)(x+8)=9x | | 135+3(25+5)=v | | -0.5x^2+35x-150=0 | | 10-n=16-2 | | 11g-17=3g+7 | | 9x^2+12x-19=2-8x | | 84=-7(v-9) | | 8x+7y=-13 | | 3x+3y+6x= | | 27x^2-13x=0 | | .125x-10=-16 | | 7x-16=x+8 | | 7n-1=-169 | | 3x^3-27x=0 | | 4x-3=4(x+5) | | 2x-1=4x+3 | | 3t-1=11 | | 2+8m=12-6m | | 8x+4=5x-11 | | .75x+2=21 | | 4x^2-2x-7=0 | | 12m+7=3m+52 | | .5y=25 | | y+10=6 | | 28-p=3p-84 | | m^2-15=0 | | 2x^2-5(x-1)=3(x-5) |